Efforts to Improve Student Focus in the Islamic Education Learning Process by Applying the Jigsaw Model Active Learning Method at SD Negeri 1701 Tanjung Ale - Hogi, Santo; Siregar, Rohyana (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to determine the effect of the application of the Jigsaw active learning method model on increasing student focus in the Islamic Education learning process at SDN 1701 Tanjung Ale. The research method used is Classroom Action Research (CAR) which consists of two cycles, with each cycle including planning, implementation, observation, and reflection. The subjects of this study were 30 fourth grade students of SDN 1701 Tanjung Ale who had difficulty in maintaining focus during the learning process. The results of the study showed that the application of the Jigsaw method was able to significantly increase student focus. In the first cycle, although there was an increase in student involvement, there were still several obstacles related to concentration that was not yet fully optimal. However, after improvements were made in the second cycle, such as providing clearer instructions, a better structure in dividing group tasks, and more intensive supervision, student focus and involvement increased rapidly. The results of the pre- and post-cycle tests showed a significant increase in understanding the material, with 85% of students experiencing increased learning outcomes. This study concludes that the Jigsaw learning method is effective in increasing student focus and participation in Islamic Education learning. With this method, students are more active in collaborating, teaching each other, and feel more responsible for their learning. Therefore, this method is recommended to be applied in other classes as a learning strategy that can improve the quality of education